Prevention and Treatment of Sports Injuries and Rehabilitative Physical Training of Wushu Athletes - Shenghai Wu; Xin Luo (Applied Bionics and Biomechanics)
This paper is aimed at exploring the characteristics of research on prevention and treatment of sports injuries and rehabilitation physical training of Wushu athletes. It also considers the application of rehabilitation physical training in the rehabilitation of Wushu athletes. By searching literature, conducting questionnaires, and combining mathematical statistics, it studies the injury prevention and rehabilitation training of Wushu athletes. This paper chooses the level of first class and above of sports, and a total of 50 elite male and female Wushu athletes were systematically trained as subjects of study. Athletes, aged 15 to 20 years, were trained for 2 to 5 years, 35 male athletes and 15 female athletes. Different from traditional rehabilitation therapy, athletes’ physical rehabilitation training is also different from traditional sports rehabilitation treatment. By evaluating the physical condition of athletes, the causes of sports injuries were analyzed, to formulate special rehabilitation training programs and carry out athletes’ rehabilitation training targeted and purposeful. Record the experimental data and analyze the experimental results. The experimental results show that physical rehabilitation training can make athletes avoid the influence of unsafe factors of sports injury, improve the safety of training, and effectively prevent sports injury. The experimental results show that physical rehabilitation training combined with rehabilitation medicine has obvious advantages, which can make Wushu athletes recover quickly without sequelae.